Food insecurity and its impact on glycaemic control in diabetic patients attending Jabulani Dumani community health centre, Gauteng province, South Africa - Kayumba B.A. Nsimbo; Neetha Erumeda; Deidre Pretorius (AOSIS, 2021)
Background: To the best of our knowledge no studies have been conducted to assess the relationship between food insecurity and poor glycaemic control in diabetic patients in peri-urban settings of the South African context. Aim: The study aimed to assess food insecurity and its relationships with glycaemic control and other patient characteristics amongst diabetic patients attending Jabulani Dumani Community Health Centre. Setting: The study was conducted in a primary healthcare facility in the south sub-district of Ekurhuleni health district, the Gauteng province, South Africa. Methods: This was a cross-sectional descriptive study involving 250 patients. Data were collected by using an interview-administered Household Food Insecurity Access Scale questionnaire. Descriptive and inferential statistical analyses by using Stata 14.0 statistical software were performed. Chi square and logistic regression tests assessed the association between socio-demographic characteristics, glycaemic control and food insecurity. Results: Amongst 250 recruited participants, 82.4% were above 50 years, 64% women, 88.8% South African citizens and 42.4% had a household size of ≥ 5 people. Sixty-four percent and 69.9% were classified as having food insecurity and poor glycaemic control, respectively. On further analysis, food insecurity was associated with unemployment (adjusted odds ratio [AOR] = 2.94; 95% confidence interval [CI]: 1.51-5.75), being a South African citizen (AOR = 1.60; 95% CI: 0.66-3.86), household size of ≥ 5 people (AOR = 1.77; 95% CI: 0.98-3.19) and uncontrolled glycaemic level (AOR = 5.38; 95% CI: 2.91-9.96). Conclusion: Food insecurity in diabetic patients constitutes a serious challenge for glycaemic control. It is critical for healthcare providers in primary care settings to ensure screening for early identification and management of food insecurity and take measures to prevent poor glycaemic control.